Whitebark pine mortality related to white pine blister rust, mountain pine beetle outbreak, and water availability. Issue 12 (8th December 2016) - Shanahan, Erin; Irvine, Kathryn M.; Thoma, David; Wilmoth, Siri; Ray, Andrew; Legg, Kristin; Shovic, Henry
Abstract: Whitebark pine ( Pinus albicaulis ) forests in the western United States have been adversely affected by an exotic pathogen ( Cronartium ribicola, causal agent of white pine blister rust), insect outbreaks ( Dendroctonus ponderosae, mountain pine beetle), and drought. We monitored individual trees from 2004 to 2013 and characterized stand‐level biophysical conditions through a mountain pine beetle epidemic in the Greater Yellowstone Ecosystem. Specifically, we investigated associations between tree‐level variables (duration and location of white pine blister rust infection, presence of mountain pine beetle, tree size, and potential interactions) with observations of individual whitebark pine tree mortality. Climate summaries indicated that cumulative growing degree days in years 2006–2008 likely contributed to a regionwide outbreak of mountain pine beetle prior to the observed peak in whitebark mortality in 2009. We show that larger whitebark pine trees were preferentially attacked and killed by mountain pine beetle and resulted in a regionwide shift to smaller size class trees. In addition, we found evidence that smaller size class trees with white pine blister rust infection experienced higher mortality than larger trees. This latter finding suggests that in the coming decades white pine blister rust may become the most probable cause of whitebark pine mortality. Our findings offered no evidence of an interactive effect of mountain pine beetle and white pine blister rust infection on whitebark pine mortality in the Greater Yellowstone Ecosystem. Interestingly, the probability of mortality was lower for larger trees attacked by mountain pine beetle in stands with higher evapotranspiration. Because evapotranspiration varies with climate and topoedaphic conditions across the region, we discuss the potential to use this improved understanding of biophysical influences on mortality to identify microrefugia that might contribute to successful whitebark pine conservation efforts. Using tree‐level observations, the National Park Service‐led Greater Yellowstone Interagency Whitebark Pine Long‐term Monitoring Program provided important ecological insight on the size‐dependent effects of white pine blister rust, mountain pine beetle, and water availability on whitebark pine mortality. This ongoing monitoring campaign will continue to offer observations that advance conservation in the Greater Yellowstone Ecosystem.